Economic modelling to evaluate smart specialisation: An analysis on research and innovation targets in Southern Europe - Javier Barbero; Olga Diukanova; Carlo Gianelle; Simone Salotti; Artur Santoalha (European Commission, Joint Research Centre (JRC), 2020)
We make the case for a technology-enabled approach to Smart Specialisation policy making in order to foster its effectiveness by proposing a novel type of economic impact assessment. We use the RHOMOLO model to gauge empirically the general equilibrium effects implied by the Smart Specialisation logic of intervention as foreseen by the policy makers designing and implementing the European Cohesion policy. More specifically, we simulate the macroeconomic effects of achieving the R&D personnel targets planned by a set of Southern European regions. We discuss the implications of the proposed methodology for future assessments of Smart Specialisation.
Keywords: C68; O38; R13; R58; 330; Smart Specialisation; ex-ante policy impact assessment; CGE models; RHOMOLO; Cohesion policy